Assessing microbial population dynamics, enzyme activities and phosphorus availability indices during phospho-compost production - F. R. Kutu; T. J. Mokase; O. A. Dada; O. H. J. Rhode (International Journal of Recycling of Organic Waste in Agriculture)
Abstract Purpose This study assessed changes in bio-quality indices and plant available P released during aerobic–thermophilic co-composting of different mix ratios of non-reactive ground phosphate rock (GPR) with poultry and cattle manures. Methods Aerobic–thermophilic co-composting of different mix ratios (5:5, 8:2, 7:3 and 9:1) of non-reactive GPR with poultry and cattle manures was carried out. Compost piles without GPR addition were included as control. Compost samples were taken at mesophilic, thermophilic, cooling–stabilization and maturing phases for microbial counts, enzyme activities and P assessment. Results Abundance of different microbial groups across the composting phases varied greatly (p < 0.001) mostly dominated by fungi that was generally more in the cattle than poultry manure-based phospho-composts. Fungi and actinomycetes counts in the composts were positively correlated with alkaline phosphatase and β-glucosidase. A strong inter-correlation between β-glucosidase and alkaline phosphatase (r = 1.000, p < 0.001) was observed, suggesting that both enzymes possess same origin. Alkaline phosphatase and β-glucosidase contents in the phospho-composts showed negative correlation with water soluble P (r = − 0.65, p < 0.001), and Bray P1 and Fe–P contents (r = − 0.15, p > 0.05) indicating inhibition of the P forms. Quantitatively higher P was obtained from poultry manure-based phospho-compost and in the 8:2 mix ratio at compost maturity. Microbial diversity and enzyme activity exerted positive impact on P mineralization and availability from the non-reactive GPR signifying the beneficial effect of co-composting. Conclusions Co-composting of P-rich non-reactive GPR with organic wastes containing variable chemical composition promotes microbial diversity during composting and increases plant available P content and compost fertilizer value.